Kepuasan Siswa Terhadap Program BK di Sekolah SMAN 1 Kapur IX - Lisa Anggraini; Yarmis Syukur; Taufik Taufik (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Service satisfaction is defined as an effort to fulfill something or make something adequate which is generally described as a feeling of pleasure or disappointment that arises towards performance (results) after being compared with expected performance. Measuring the level of student satisfaction towards services in schools is an important element in the school's efforts to provide the best, efficient and effective services for students. This study aims to evaluate the effectiveness of the Guidance and Counseling (BK) program in schools. This survey involved a number of BK teachers and students from several schools in certain areas. The research method used was qualitative with an open questionnaire instrument, namely a structured interview to measure various aspects of the BK program, including service quality, student involvement, and the impact on students' academic and emotional development. The survey results showed that most students and BK teachers felt that the BK program in schools had been running quite well, but there were still some areas that needed improvement, such as the availability of resources and further training for counselors. In addition, there was a positive correlation between the frequency of student involvement in BK sessions with an increase in their academic achievement and emotional well-being. This study provides recommendations for improving the BK program in schools, including increasing training for counselors and strengthening support from the school.